Conditional Cooperation and Turn-Taking in Parental Care - Johnstone, Rufus A.; Savage, James L. (Frontiers in Ecology and Evolution, 2019)
Sexual conflict is inescapable when two parents care for offspring, because providing care is personally costly, while the benefits of successful reproduction are shared. Previous models that treat parental investment as a continuous trait, with stable levels of effort negotiated between parents over evolutionary or behavioural time, generally predict that sexual conflict will lead to under-investment in the young, as each parent stands to gain by leaving its partner to bear a greater share of the costs of care. More recently, a model of parental investment as repeated discrete contributions suggested that a more efficient outcome can be reached through parents adopting a simple strategy of conditional cooperation by ‘turn-taking’: only investing after each contribution by their partner. However, while empirical work suggests that parental visits are significantly alternated in a number of natural systems, all examples thus far exhibit imperfect turn-taking rather than the strict rule predicted by theory. To help bridge this gap, we here present a more realistic mathematical model of parental turn-taking, incorporating (i) errors in parents’ ability to monitor the contributions of their partner, (ii) time-dependent costs and benefits of delivering care, (iii) differences between partners in payoffs (and consequently in behaviour), (iv) differences between partners in the accuracy with which they can monitor one another’s behaviour, and (v) shared costs of care. We illustrate how the degree of conditional cooperation is influenced by each of these factors, and discuss ways in which our model could be tested empirically.